Histological, physiological, and transcriptional alterations in the liver of yellowfin seabream Acanthopagrus latus under different salinity conditions - Yinjun Ye; Naiyu Xie; Xuanguang Liang; Huixin Zhao; Genmei Lin (Journal of Oceanology and Limnology, 2026)

Visualizing the Landscape and Evolution of Phosphorus Research in Saline-Alkali Soils by Scientometric Analysis - Pingping Zhang; Yuhang Li; Lin Liao; Junna Hu; Genmei Wang; Huanchao Zhang; Jian Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Coupled acidification-nitrification dynamics in eutrophic estuarine waters - Hongming Yao; Bingqian Zhu; Ming Zhu; Yanni Ren; Fei Chen; Dongyao Sun; Genmei Lin; Xianbiao Lin (Water Research, 2026)

Spatial patterns of total and methane-cycling microbial communities in surface sediments of the eastern Guangdong coast in summer - Jianbo Yao; Huixin Zhao; Wangwang Ye; Yinjun Ye; Genmei Lin (Marine Environmental Research, 2025)

Characterization of Gut and Gill Microbiomes in Fast-Growing Pacific White Shrimp Penaeus vannamei - Zhenqiang Fu; Qinglong Chen; Yinjun Ye; Huixin Zhao; Genmei Lin; Jianguo Lu (Journal of Ocean University of China, 2025)

Transcriptome sequencing reveals gene expression patterns in non-symbiotic tissues of the cold seep clam Phreagena okutanii - Yinjun Ye; Genmei Lin; Huixin Zhao; Xuanguang Liang; Junrou Huang; Jianguo Lu (Acta Oceanologica Sinica, 2025)

Functional and microbial insights into the gill symbiosis and metal tolerance of the cold seep mussel Gigantidas haimaensis - Xuanguang Liang; Mingmin Du; Yuxin Qin; Wenlong Cai; Junrou Huang; Genmei Lin; Jianguo Lu (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Microbial community structure and functional diversity affected by soil depth, tidal levels, and stand ages in restored Sonneratia apetala mangroves - Wenxiao Su; Zeyu Lin; Yiyuan Lin; Genmei Lin; Long Wei; Meilin Wu; Jianxiang Feng (Estuarine, Coastal and Shelf Science, 2025)

Comparative transcriptome analysis revealed host defense responses in endosymbiotic gill of Bathymodiolus mussels inhabiting cold seeps and hydrothermal vents - Genmei Lin; Boxian Wen; Junrou Huang; Xuanguang Liang; Cuiling Xu; Ye Chen; Nengyou Wu; Jianguo Lu (Journal of Oceanology and Limnology, 2025)

Responses of microbial communities and greenhouse gas production to land use change in mangrove wetland sediments - Xianbiao Lin; Bingqian Zhu; Yongyi Peng; Genmei Lin; Dongyao Sun; Wangwang Ye (Limnology and Oceanography, 2025)
Tidal wetland reclamation is a worldwide issue that profoundly alters ecological functions and ecosystem service provisions; however, its impacts on sediment microbial communities and functions remain poorly understood. Here, we investigated the spatial and seasonal patterns of greenhouse gas (GHG) production in response to land use change in mangrove wetlands and elucidated the underlying mechanisms by integrating environmental parameters and microbial community characteristics. In the time period studied, land use change substantially reduced the sediment organic matter content, microbial community richness and diversity, and CO 2 production rates. Converting mangroves to drier land cover types, namely orchard and vegetable field, significantly diminished reducing substrates (sulfide, Fe 2+ , and NH 4 + ), microbial network complexity and stability, and CH 4 production rates, while increasing N 2 O production rates. In contrast, these parameters showed the opposite trend following the conversion of mangroves to flooded aquaculture pond. Overall GHG production rate in mangrove wetlands was 399.8 mg CO 2 e kg −1 d −1 , which respectively decreased by 68.83%, 69.86%, and 30.84% in orchard, vegetable field, and aquaculture pond. Microbial community richness and network complexity and stability were strongly related to the production rates of CH 4 and N 2 O, rather than CO 2 , which can be better indicators of specialized functions (CH 4 and N 2 O production). Therefore, preserving microbial “interaction” could be important to mitigate the negative effects of microbial community richness and diversity loss caused by human activities in aquatic environments. Future research should consider environmental conditions and microbial community diversity, composition, interactions, and activities to gain a comprehensive understanding of ecosystem functions.

Transcriptomic Responses and Larval-Stage Growth of Protandrous Yellowfin Seabream (Acanthopagrus Latus) to Different Polyethylene Microplastics Exposure - Meng Xu; Wenyu Fang; Genmei Lin; Xiaoshan Zhu; Jianguo Lu (Marine Biotechnology, 2024)

Nitrogen mineralization and immobilization in surface sediments of coastal reclaimed aquaculture ecosystems - Xianbiao Lin; Genmei Lin; Yijie Zheng; Wenjing Li; Peng Guo; Shiyuan Fan; Tiantian Kong; Dongfan Tian; Dongyao Sun; Zhuo Shen (Frontiers in Marine Science, 2023)
Sediment nitrogen (N) mineralization and immobilization are two crucial processes driven by microorganisms, which may play significant roles in the regulation of water quality in aquaculture ecosystems. However, limited information is available about the quantitative importance of sedimentary N mineralization and immobilization in coastal aquaculture systems. Here, a combination of incubation experiments with a 15 N isotope dilution technique were employed, aiming to quantify N mineralization and immobilization processes in surface sediments (0–5 cm) of three types of aquaculture ecosystems (seabass, white shrimp, and green crab ponds) reclaimed within the western bank of the Pearl River Estuary. Our results showed that no significant difference in sediment N mineralization and immobilization rates, microbial abundances, and organic matter among different aquaculture types on small-scale range. Meanwhile, prolonged pond-drying significant reduced sediment N mineralization and immobilization rates, bacterial abundances, organic matter, moisture content, ferrous ion (Fe 2+ ), Fe 2+ /Fe 3+ , and ammonium (NH 4 + ), while not strongly altered sediment percentage of NH 4 + mineralized per day (PAM), relative ammonium immobilization (RAI), fungal abundances, TOC/TN, nitrate (NO 3 − ), and δ 13 C org . N mineralization and immobilization rates were both significantly related to overlying water NO 3 − , as well as sediment moisture content, bulk density, organic matter, Fe 2+ , and microbial abundances. In addition, the total mineralized and immobilized N in aquaculture surface sediments from the Guangdong-Hong Kong-Macao Greater Bay Area were estimated to be approximately 4.55×10 4 and 3.68×10 4 t N yr -1 , respectively. Higher N mineralization relative to N immobilized fluxes indicated that the sediment serves as an important source of eutrophication in reclaimed aquaculture system of coastal wetlands.

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

Chromosome-level Genome Assembly of Acanthopagrus latus Provides Insights into Salinity Stress Adaptation of Sparidae - Jianguo Lu; Dong Gao; Ying Sims; Wenyu Fang; Joanna Collins; James Torrance; Genmei Lin; Jingui Xie; Jian Liu; Kerstin Howe (Marine Biotechnology, 2022)

Hypoosmotic stress induced functional alternations of intestinal barrier integrity, inflammatory reactions, and neurotransmission along gut-brain axis in the yellowfin seabream (Acanthopagrus latus) - Genmei Lin; Shizhu Li; Junrou Huang; Dong Gao; Jianguo Lu (Fish Physiology and Biochemistry, 2021)

Transcriptome Profiling Reveals the Sexual Dimorphism of Gene Expression Patterns during Gonad Differentiation in the Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Genmei Lin; Dong Gao; Jianguo Lu; Xiaowen Sun (Marine Biotechnology, 2021)

Construction of High-Density Genetic Map and Mapping of Sex-Related Loci in the Yellow Catfish (Pelteobagrus fulvidraco) - Dong Gao; Min Zheng; Genmei Lin; Wenyu Fang; Jing Huang; Jianguo Lu; Xiaowen Sun (Marine Biotechnology, 2020)

Structural Variation Analysis of Mutated Nannochloropsis oceanica Caused by Zeocin Through Genome Re-Sequencing - Genmei Lin; Zhongyi Zhang; Li Guo; Haiyan Ding; Guanpin Yang (Journal of Ocean University of China, 2018)

Verification of mutagen function of Zeocin in Nannochloropsis oceanica through transcriptome analysis - Genmei Lin; Yamei Wang; Li Guo; Haiyan Ding; Yongmei Hu; Sijie Liang; Zhongyi Zhang; Guanpin Yang (Journal of Ocean University of China, 2017)